Pengaruh Literasi Keuangan, Pembiayaan Murabahah dan Mudharabah Terhadap Pengembangan Keunggulan Kompetitif Sektor UMKM di Mojokerto: Studi Kasus pada Bank Syariah Mandiri KCP Mojokerto - Wilda Rifa Ardiana; Lutvi Alamsyah; Ahmad Mukhlisuddin (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
This study aims to determine the effect of financial literacy, murabahah and mudharabah financing on the competitive advantage of the MSME sector in Mojokerto. The research method used in this research is quantitative research methods using primary data. The sampling technique used non probability sampling, in order to obtain 62 respondents. Data analysis in this study used multiple linear regression analysis through SPSS version 20. The results of the study indicate that financial literacy has an effect on the development of competitive advantage in the MSME sector in Mojokerto. Murabahah financing has no effect on the development of a competitive advantage in the MSME sector in Mojokerto. Mudharabah financing has an effect on the development of a competitive advantage in the MSME sector in Mojokerto.